The Development of Research on Marketing Engagement a Bibliometric Analysis - Syafira Khania; Milenia Inez Safitri; Adi Setiawan (Jurnal Informasi dan Teknologi, 2025)
Engagement marketing has emerged as a strategic approach that emphasizes interactive, personalized, and value-driven relationships between brands and consumers. The rapid growth of digital technologies, social media, and smart devices has fundamentally transformed customer engagement, making it a central element of contemporary marketing strategies. This study aims to examine the evolution, research trends, and intellectual structure of engagement marketing literature, with particular emphasis on its relationship with digital transformation and small and medium-sized enterprises (SMEs). A qualitative historical approach combined with bibliometric analysis was employed to systematically evaluate publications indexed in Scopus, Emerald, Springer, ProQuest, Web of Science, and ScienceDirect. Article retrieval was conducted using the Publish or Perish software for the period 1956–2025, applying relevant keywords related to engagement marketing, internet marketing, business models, and brand engagement. After applying inclusion criteria, including English-language journal articles in management, business, economics, social sciences, information systems, and entrepreneurship, a total of 2,302 publications were analyzed. Bibliometric mapping and visualization were performed using VOSviewer to generate network, overlay, and density maps that reveal research collaborations, thematic evolution, and emerging research opportunities. The findings indicate a substantial increase in engagement marketing publications, particularly between 2016 and 2022, reflecting the accelerated adoption of digital technologies and electronic markets. Collaboration analysis demonstrates strong and expanding research networks among scholars, while overlay visualization highlights growing attention to business strategy and digital transformation. Density visualization further identifies several underexplored research themes, indicating promising opportunities for future investigation. This study provides a comprehensive scientific mapping of engagement marketing research and offers strategic directions for future studies focusing on digital transformation, customer engagement, innovation, and sustainable SME competitiveness